RESILSTIGMA. Resilience to self-stigmatization experienced by people living with HIV: Which self-reported factors improve awareness among health workers? - Christine Jacomet; Cécile Miele; Emilie Goncalves; Céline Lambert; Clément Belletier; Françoise Linard; Josiane Phalip-Le Besnerais; Pierre Dellamonica; Michael Dambrun (PLoS ONE, 2025)
Background Self-stigmatization is the process by which environmental stigmas are internalized. It leads to a decline in self-esteem, isolation, denial and risk behavior, and impairs quality of life. The aims of our study were to investigate the psychological, social and medical factors, in particular psychological flexibility and its defusion component, that are associated with resilience to self-stigmatization in people living with HIV (PLHIV), and to assess clinicians’ perceptions of the condition. Methods A multicenter observational study was conducted in France using self-reports from PLHIV consulted between January 15, 2022 and June 15, 2022 and from professionals responsible for their care (study registration number 2021-A01588-33/SI:21.02814.000036). Self-stigmatization was measured by examining four domains: perceived stigma, anticipated stigma, internalized stigma and enacted stigma. Results Self-reports were collected from 45 hospital wards, 666 from PLHIV, of whom 71% were male with a mean age of 53 +/- 12.6 years, and 131 from health professionals, of whom 72.5% were clinicians. A total of 279 PLHIV (42%) reported items of self-stigmatization. Multivariable analysis showed that self-stigmatization was significantly associated with major depression (OR: 3.59, 95% CI: 1.19 to 10.80, p = 0.02), psychological inflexibility (OR: 1.53, 95% CI: 1.19 to 1.97, p = 0.001), and parental support deficit in childhood (OR parental support: 0.63, 95% CI: 0.40 to 0.98, p = 0.04). Among the dimensions of psychological inflexibility associated with HIV self-stigma, only fusion was positively associated (p<0.01). The proportion of PLHIV experiencing self-stigma was accurately estimated by only 31 (23.7%) health workers. Those health workers who did not minimize the prevalence of self-stigmatization among PLHIV had no particular characteristics. Conclusions While the best means to combat self-stigmatization would be a social-ecological approach, it is fundamental to target in parallel individual vulnerability and protective factors accessible to health workers’ interventions. Psychiatric care and/or the new cognitive-behavioral therapies could be offered more often as part of personalized care.